Boys should not be overlooked: Sexual violence victimization and associated factors among school-going adolescents in urban Ghana - Quarshie, E.N-B. (Child Abuse & Neglect, 2021)
Background: Adolescent sexual violence victimization is still less researched in countries within sub-Saharan Africa, including Ghana. Objectives: To estimate the 12-month prevalence of sexual violence victimization and describe the differences and commonalities in the associated factors between school-going boys and girls in urban Ghana. Participants and setting: Students (n = 1692) aged 13–19 years attending Second Cycle Schools in the Greater Accra Region of Ghana participated in this study. Methods: This is a cross-sectional survey involving the use of a self-report anonymous questionnaire. Items measuring sexual violence victimization and correlates were adopted from the 2012 WHO–Global School-based Student Health Survey. Data analysis involved bivariable and multivariable approaches. Results: Overall, 17.6% (95% confidence interval [CI] 15.7, 19.4) adolescents (males = 10.4% [95% CI 8.3, 13.6]; females = 24.3% [95% CI 21.5, 27.3]) reported sexual violence victimization during the previous 12 months. Girls (compared to boys) were nearly three times more likely to report sexual violence victimization (aOR = 2.74, 95% CI 2.01, 3.74, p < 0.001). Breakup, sexual minority status, and conflict with parents were uniquely associated with sexual violence victimization among females. Regardless of gender, adolescents who were in a romantic relationship (aOR = 1.63, 95% CI 1.19, 2.24, p = 0.002) and reported physical abuse victimization (aOR = 1.84, 95% CI 1.36, 2.49, p < 0.001) were more likely to report sexual violence victimization. Conclusions: The prevalence of sexual violence victimization among school-going adolescents in urban Ghana compares with estimates from sub-Saharan Africa, but also warrants the need for universal and targeted prevention regimes against the offence in both boys and girls.
Research Article
Keywords: Adolescents; Child sexual abuse; Sexual abuse; Sexual violence; Sexual violence victimization